Catalytic enantioselective synthesis of tetrasubstituted chromanones via palladium-catalyzed asymmetric conjugate arylation using chiral pyridine-dihydroisoquinoline ligands. Issue 18 (20th April 2020) - Baek, Doohyun; Ryu, Huijeong; Ryu, Ji Yeon; Lee, Junseong; Stoltz, Brian M.; Hong, Sukwon
Abstract : The first palladium-catalyzed enantioselective conjugate addition reactions of arylboronic acids to 2-substituted chromones with chiral pyridine-dihydroisoquinoline ligands have been developed. Abstract : Highly enantioselective conjugate addition reactions of arylboronic acids to 2-substituted chromones catalyzed by palladium complexes with new chiral Pyridine-Dihydroisoquinoline (PyDHIQ) ligands have been developed. These reactions provide highly enantioselective access to chromanones containing tetrasubstituted stereocenters. Various arylboronic acids and 2-substituted chromones can be used in the catalytic reaction to afford the chiral tetrasubstituted chromanones in good yields and excellent enantioselectivities (25 examples, up to 98% yields, up to 99% ee).